PENGARUH PENGGUNAAN MEDIA FLASH CARD AUDIO VISUAL TERHADAP KEMAMPUAN MEMBACA PERMULAAN - Ilham Asmaryadi, Ahmad; Amar Salahuddin; Tuti Hariani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Beginning reading is a fundamental skill that must be mastered by elementary school students because it serves as the foundation for learning various subjects. Based on preliminary observations conducted in Grade I of SDN 06 Sitiung, several students still experienced difficulties in recognizing letters, reading syllables, words, and simple sentences. Therefore, this study aimed to determine the effect of using audiovisual flash card media on the beginning reading skills of first-grade students at SDN 06 Sitiung. This research employed a quantitative approach with a pre-experimental method using a One-Group Pretest–Posttest Design. The population and sample consisted of 23 first-grade students selected through a saturated sampling technique. Data were collected through beginning reading tests administered before and after the implementation of audiovisual flash card media. The collected data were analyzed using the Shapiro–Wilk normality test and paired sample t-test with the assistance of SPSS version 20. The results indicated that students’ beginning reading skills improved significantly after the treatment. The mean pretest score was 66.869, while the mean posttest score increased to 84.130. These findings demonstrate that the use of audiovisual flash card media has a positive effect on improving beginning reading skills among first-grade students at SDN 06 Sitiung.